PRESENTATION OF LONG—TERM LEASE LIABILITIES IN THE BALANCE SHEET. - Myers, John H. (The Accounting Review, 1948)
The article presents information on the presentation of long term lease liabilities in the balance sheets. The balance sheet is an important statement in its own right, even granting such inadequacies in satisfying certain purposes as recording different fixed assets at different price level. For one thing it is useful in studying the financial condition of a company. A most important point in a study of short-term condition is a consideration of the current-asset and current-liability sections. In a study of long-term financial condition the entire liability side is important in that it represents claims against the company and indicates the source of the funds with which the assets were obtained. All of the information presented on the income statement and balance sheet could he presented in text form. In recent years a new business procedure has been evolving which requires a reappraisal of today's body of conventions and principles. It is the acquisition of plant and equipment through use of a long-term lease rather than through the more traditional method of outright purchase frequently coupled with a long-term mortgage loan.